Telerilevamento e modelli meteo-climatologici per le Isole Urbane di Calore (GEOmedia, 2010)
Remote sensing and microclimatology models for theUrban Heat IslandsAn Urban Heat Island (UHI) is a metropolitan area which is significantly warmer than its surrounding rural areas. The main cause of the UHI is the modification of the land surface by urban development. The most disastrous consequences are the Heat Waves that periodically strike the city during summer. With the rise of thermal remote sensing technology it has become possible to study the UHI by means of satellite and airborne platforms, giving new elements for understanding the effect and its causes, using a combination of remote sensing observations and models of urban micro meteorology. UHI is an ESA funded project lead by Planetek Italia and carried out by a Consortium of private companies and research institutes in 10 European cities.